Study of coral reef for marine ecotourism development based on region suitability and carrying capacity in Marsegu Island Nature Tourism Park, Maluku, Indonesia - HENDERINA LELLOLTERY; SATYAWAN PUDYATMOKO; CHAFID FANDELLI; MUHAMAD BAIQUNI (Biodiversitas Journal of Biological Diversity, 2018)
Lelloltery H, Pudyatmoko S, Fandelli C, Baiquni M. 2018. Study of coral reef for marine ecotourism development based on region suitability and carrying capacity in Marsegu Island Nature Tourism Park, Maluku, Indonesia. Biodiversitas 19: 1089-1096. The objectives of the research were to identify the potential of marine natural resources as the object and attraction of marine ecotourism, and to compile the development plan at Marsegu Island Nature Tourism Park (NTP) based on the Tourism Suitability Index (TSI) and carrying capacity. Data collection included coral reef and fish type using the Line Intercept Transect (LIT) method. Data were analyzed using the tourism suitability index and analysis of physical carrying capacity of the area. The results showed the potential of marine resources covering the coral reefs including 45 species within 23 genera from 14 families with 12 coral lifeforms. A high diversity of reef fish was found, documenting 129 species of fish within 60 genera from 22 families. The analysis result of the tourism suitability index (TSI) in the snorkeling category was 74.79% with a carrying capacity of 4,092 person(s)/day and the TSI of diving was 67.32% with a physical carrying capacity of 1,855 person(s)/day. The analysis showed that the area around Marsegu Island NTP is "suitable" for ecotourism activities and does not exceed the carrying capacity of the area. The strategy for marine ecotourism management needs to be completed, including elements such as determining the number of tourists that can be supported per day (based on limiting the number of divers/snorkelers per day), implementing boat moorings so coral is not damaged by anchors, making sure tourism operators brief divers/snorkelers not to touch, stand on or break the coral, and ensuring the tour operator is the organization responsible for the continuous monitoring of marine ecotourism activities and protection of dive sites.